Selection for Loss of RpoS in Cronobacter sakazakii by Growth in the Presence of Acetate as a Carbon Source - Álvarez-Ordóñez, Avelino (American Society for Microbiology, 2013)
We demonstrate that growth of Cronobacter sakazakii in the presence of acetate as a carbon source promotes loss of RpoS, with a consequent reduction in stress tolerance. This suggests that C. sakazakii is capable of regulating cell fitness through mutation of the rpoS gene.